After About: Unlearning Colonialism, Ethical Relationality, and the Possibilities for Pedagogical Praxis - Howell, Lisa (Université d'Ottawa / University of Ottawa, 2022)
In 2015, the Truth and Reconciliation Commission of Canada (TRC) called on Ministries of Education, Faculties of Education, school administrators, and K-12 teachers to integrate Indigenous knowledges and pedagogies across the school curriculum. The TRC explicitly emphasized that education would be the intergenerational key to reconciliation in Canada and most provinces and territories quickly implemented curricula and developed resources to respond to the Calls to Action. Despite this mandate and these commitments, many teachers and teacher candidates continue to report that they do not have the skills, knowledge, or confidence to teach about the history of the Indian Residential Schooling system, Indigenous knowledges, or reconciliation. Research suggests that teacher resistance to "difficult knowledge" is a crucial contributing factor toward teachers avoiding, ignoring, and dismissing reconciliation work and upholding colonial logics. Moreover, teacher candidates and teachers often rely on the inaccurate and incomplete narratives they have learned about Canadians and First Nations, Inuit, and Métis Peoples. This impacts what and how they teach about these relationships, complicating the transformational changes the TRC urgently called for. How, then, might teachers unlearn these colonial stories and move from learning about Indigenous peoples to learning from them? Drawing on Donald’s concept of "ethical relationality", this study employed a qualitative approach to conduct conversational interviews with teacher candidates, teachers, staff, and students at two research sites. This study asks, "What are the curricular and pedagogical significances of ethical relationality to processes of unlearning colonialism?" Using a hermeneutic approach to interpret the stories shared, this study weaved within and between the landscapes of home and place. Findings reveal that teachers who experience supportive, multi-layered, and extended opportunities to unlearn settler colonialism and learn Indigenous wisdom traditions and ...